Language in contact: The case of the Fulbe dialect of Kejom (Babanki) - (:unkn) unknown (My University, 2010)
This paper describes the variety of Babanki (henceforth called Kejom) spoken by native Fulfulde speakers born and raised in Kejom communities. Kejom is a Center Ring Grassfields Bantu language spoken in two villages (Kejom Ketinguh and Kejom Keku) in northwestern Cameroon. This paper describes the practice in Kejom Ketinguh. The Fulɓe are Fulfulde speakers of Adamawa origin who migrated from northern Cameroon and settled in Kejom more than 50 years ago. Peaceful coexistence between the two groups has encouraged young Fulɓe to learn the Kejom language and to use it when interacting with Kejom people. Comparison of the speech of Fulɓe and native speakers of Kejom revealed that the Kejom spoken by the Fulɓe (the Fulɓe dialect) contains phonological, morphological, syntactic, and lexical deviations from the standard variety spoken by Kejom people. In addition to Fulfulde (the Fulɓe mother tongue), Cameroon Pidgin English (their second language) has also influenced the Fulɓe dialect of Kejom. We argue in this paper that the Fulɓe prefer to rely on Cameroon Pidgin English to fill most communication gaps with native Kejom speakers, because this widely used language is common to both communities.
Keywords: African Research